2021
DOI: 10.1186/s12920-021-00889-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptome and proteome analyses identify novel regulatory network of nucleus pulposus cells in intervertebral disc degeneration

Abstract: Background Degeneration of intervertebral disc is a major cause of lower back pain and neck pain. Studies have tried to unveil the regulatory network using either transcriptomic or proteomic analysis. However, neither have fully elucidated the exact mechanism of degeneration process. Since post-transcriptional regulation may affect gene expression by modulating the translational process of mRNA to protein product, a combined transcriptomic and proteomic study may provide more insight into the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(72 reference statements)
2
7
0
Order By: Relevance
“…Although the correlation between the proteome and transcriptome was poor ( R = 0.225 and 0.05), a relatively higher positive correlation was identified ( R = 0.51 and 0.60) for the DEGs and DAPs, regulated in the same direction, in UVB_vs_Control and UVA_vs_Control, respectively (Figure S4c–f). These results were consistent with many previous studies, which integrated transcriptome and proteome to investigate molecular mechanisms in a variety of organisms, including Chinese hamster ovary cells, nucleus pulposus cells and plants (43–46). These were probably attributed to the complex post‐transcriptional or translational regulation (45,47).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the correlation between the proteome and transcriptome was poor ( R = 0.225 and 0.05), a relatively higher positive correlation was identified ( R = 0.51 and 0.60) for the DEGs and DAPs, regulated in the same direction, in UVB_vs_Control and UVA_vs_Control, respectively (Figure S4c–f). These results were consistent with many previous studies, which integrated transcriptome and proteome to investigate molecular mechanisms in a variety of organisms, including Chinese hamster ovary cells, nucleus pulposus cells and plants (43–46). These were probably attributed to the complex post‐transcriptional or translational regulation (45,47).…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with many previous studies, which integrated transcriptome and proteome to investigate molecular mechanisms in a variety of organisms, including Chinese hamster ovary cells, nucleus pulposus cells and plants (43–46). These were probably attributed to the complex post‐transcriptional or translational regulation (45,47). To a certain extent, the DAPs identified from comparative proteomic analysis implicated that these proteins might contribute to the changes in cell functions or phenotypes.…”
Section: Discussionsupporting
confidence: 93%
“…First, the data used were downloaded from a public database, and it was not possible to assess whether there were entry errors. Also, there exist differences in the enriched gene functions and pathways of the differentially expressed genes between mRNA and protein data, and this study focused only on mRNA datasets ( Xu et al, 2021 ). Second, our study only focused on the genes that were identified as differentially expressed in datasets.…”
Section: Discussionmentioning
confidence: 99%
“… Xu et al (2021) created a regulatory network behind IDD by combining transcriptomic and proteomic analysis. They hypothesized that post-transcriptional regulation could have an effect on protein content, thus, if a gene presents elevated mRNA and protein levels, it could be implicated in IDD.…”
Section: Research Methods For Exploring the Inflammatory Or Catabolic...mentioning
confidence: 99%